1995
DOI: 10.1007/bf00800604
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic approach to reflex sympathetic dystrophy after fracture: radiography or bone scintigraphy?

Abstract: The aim of this paper was to compare the value of bone scintigraphy and radiography in the early diagnosis of post-fracture reflex sympathetic dystrophy (RSD). Thirty-seven adult patients with post-fracture RSD (28 in the first and nine in the second clinical stage of RSD), as well as seven patients with fracture but without RSD (control group), were investigated by radiography and bone scintigraphy. All of them were immobilized (duration of immobilization: 4-22 weeks). In 21 persons three phase bone scintigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 12 publications
0
18
0
4
Order By: Relevance
“…TPBS is one of widely used imaging studies in CRPS-1. Although osteoporosis on simple X-ray or marrow edema and soft tissue swelling on MRI are supportive findings for CRPS-1, they are not as sensitive or specific as TPBS [16]. However, there are wide variations in the diagnostic sensitivity and specificity of TPBS [8-10, 16, 20-23], and some authors argued that TPBS cannot provide useful information for making a clinical diagnosis of CRPS-1 [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TPBS is one of widely used imaging studies in CRPS-1. Although osteoporosis on simple X-ray or marrow edema and soft tissue swelling on MRI are supportive findings for CRPS-1, they are not as sensitive or specific as TPBS [16]. However, there are wide variations in the diagnostic sensitivity and specificity of TPBS [8-10, 16, 20-23], and some authors argued that TPBS cannot provide useful information for making a clinical diagnosis of CRPS-1 [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that CRPS-1 has clinical stages [25] and TPBS findings change according to clinical stages [15][16][17]. It was reported that F/P normalizes or even decreases, and afterward, DU normalizes as the disease progresses [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die radiologische Erscheinung beinhaltet neben der Demineralisation des gelenknahen trabekulären Knochens auch endostale, intrakortikale, subperiostale und subchondrale Resorptionsvorgänge [77]. Vor allem in frühen Stadien der Erkrankungen ist die Knochenszintigraphie von diagnostischer Bedeutung [101].…”
unclassified
“…De acordo com Todorovic-Tirnanic et al (1995), a capacidade diagnóstica da radiografia simples é igual ou superior a cintilografia óssea após a segunda fase da doença.…”
Section: Radiografia Convencional (Raio-x)unclassified